2008
DOI: 10.1093/brief-treatment/mhn013
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Success: Solution-Focused Brief Therapy

Abstract: Results of several studies suggest that traumas need not be debilitating and that most people are resilient and even grow in the wake of a trauma. Understanding and highlighting the sources of this resilience and posttraumatic growth and focusing on hope and optimism help professionals foster these strengths in their clients, as opposed to focusing on what is wrong with them, which can have a discouraging effect. From a solution-focused perspective, the focus in treatment shifts from posttraumatic stress to po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 6 publications
2
30
0
3
Order By: Relevance
“…Algoe, Haidt, and Gable (2008) concluded that teaching positive thinking techniques and skills to individuals improved positive relationships with themselves and focusing on the positive aspects increased self-confidence and self-esteem. Furthermore, Ebadi, Soudani, Faghihi, Hosseinpour (2011), Bannink (2008, Wang and Lim (2008), and Ho, Cheung, and Cheung (2010) concluded that teaching positive thinking also increased the happiness and reduces depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Algoe, Haidt, and Gable (2008) concluded that teaching positive thinking techniques and skills to individuals improved positive relationships with themselves and focusing on the positive aspects increased self-confidence and self-esteem. Furthermore, Ebadi, Soudani, Faghihi, Hosseinpour (2011), Bannink (2008, Wang and Lim (2008), and Ho, Cheung, and Cheung (2010) concluded that teaching positive thinking also increased the happiness and reduces depression.…”
Section: Discussionmentioning
confidence: 99%
“…This approach focuses on positive processes and individual's abilities and recommends the therapists to consider the positive processes of their clients rarely occurring in their lives (Seligman, Rashid, & Parks, 2006). The results of Bannink (2008) study showed that positive attitude increased the positive thinking of female students. Studies of Also Lee, Cohen, Edgar, Laizner, and Gagnon (2006) and Alberto and Joyner (2008) showed that training positive attitude increased mental health, hopefulness, selfefficacy, self-esteem, and reduced stress in women.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, the client relinquishes competencies to the therapist ('you tell me what I should do'), a pitfall that can be avoided with SFBT. 10 …”
Section: Crisis Interventionmentioning
confidence: 99%
“…Positive attitudeis used because it attends to positive parts of the life emphasizing also on beliefs, understanding and thought effects on performance (Seligman, 2005). The results of Kazemian (2010), Asadollahi (2005), Tracy (2008) and Bannink (2008) showed that regarding the aspects of positive attitude increased the positive attitude and positive thinking of female students. Also and Alberto and Joyner (2010) showed that training positive attitude increases mental health, hopefulness, self-efficacy, self-esteem and stress reduction of women.…”
Section: Introductionmentioning
confidence: 99%